CONFLICT OVERCOMING IN THE "TEACHER-STUDENT" SYSTEM BY MEANS HUMANISTIC APPROACH TO THE ORGANIZATION PEDAGOGICAL PROCESS - L.Yu. Puzanova (Academy of Cognitive and Natural Sciences, 2006)
The possibilités of the humanistic approach to the organization of pedagogikal process in overcoming the conflict relations between the teacher and tne pupil are considered in this article.